Mycobacterium Tuberculosis-Associated Hemophagocytic Syndrome in Systemic Lupus Erythematosus: A Case Report - Hussein HALABI; Waleed HAFIZ; Mayadah BAWAYAN; Abdulghani MAULAWI; Hani ALMOALLIM3 (Archives of Rheumatology, 2012)
Mycobacterium tuberculosis infection is a complex, potentially life-threatening disease. Multiple hematological abnormalities may be seen in tuberculosis infection. However, Mycobacterium tuberculosis-associated hemophagocytic syndrome (HPS) in systemic lupus erythematosus (SLE) patients is quite rare. In this article, we report a 47-year-old female case of Mycobacterium tuberculosis-associated HPS in a patient with SLE. The patient had diffuse alveolar hemorrhage, myocarditis, and acute renal failure and required 17 sessions of plasma exchange and six sessions of cyclophosphamide. She also presented with fever, hypotension, desaturation, hepatosplenomegally, and pancytopenia which required intubation. Broncho-alveolar lavage revealed the diagnosis of Mycobacterium tuberculosis. The patient was initiated with rifampicin, ethambutol, pyrazinamide, moxifloxacin and amikacin. There was no indication of any SLE flare; however she continued to be febrile and pancytopenic. Her ferritin level was observed to be elevated. A bone marrow examination also showed hemophagocytosis plus multiple granulomas. Despite active treatment, the patient died due to septic shock and multi-organ failure. Mycobacterium tuberculosis has the potential to induce HPS in SLE patients; therefore, accurate diagnosis and aggressive therapy are critical. All SLE patients should be screened for latent tuberculosis and managed accordingly.